Pushing the boundaries: molecular dynamics simulations of complex biological membranes - Parton, D (2011)
A range of simulations have been conducted to investigate the behaviour of a diverse set of complex biological membrane systems. The processes of interest have required simulations over extended time and length scales, but without sacrifice of molecular detail. For this reason, the primary technique used has been coarse-grained molecular dynamics (CG MD) simulations, in which small groups of atoms are combined into lower-resolution CG particles. The increased computational efficiency of this technique has allowed simulations with time scales of microseconds, and length scales of hundreds of nm. The membrane-permeabilizing action of the antimicrobial peptide maculatin 1.1 was investigated. This short α-helical peptide is thought to kill bacteria by permeabilizing the plasma membrane, but the exact mechanism has not been confirmed. Multiscale (CG and atomistic) simulations show that maculatin can insert into membranes to form disordered, water-permeable aggregates, while CG simulations of large numbers of peptides resulted in substantial deformation of lipid vesicles. The simulations imply that both pore-forming and lytic mechanisms are available to maculatin 1.1, and that the predominance of either depends on conditions such as peptide concentration and membrane composition. A generalized study of membrane protein aggregation was conducted via CG simulations of lipid bilayers containing multiple copies of model transmembrane proteins: either α-helical bundles or β-barrels. By varying the lipid tail length and the membrane type (planar bilayer or spherical vesicle), the simulations display protein aggregation ranging from negligible to extensive; they show how this biologically important process is modulated by hydrophobic mismatch, membrane curvature, and the structural class or orientation of the protein. The association of influenza hemagglutinin (HA) with putative lipid rafts was investigated by simulating aggregates of HA in a domain-forming membrane. The CG MD study addressed an important limitation of model membrane experiments by investigating the influence of high local protein concentration on membrane phase behaviour. The simulations showed attenuated diffusion of unsaturated lipids within HA aggregates, leading to spontaneous accumulation of raft-type lipids (saturated lipids and cholesterol). A CG model of the entire influenza viral envelope was constructed in realistic dimensions, comprising the three types of viral envelope protein (HA, neuraminidase and M2) inserted into a large lipid vesicle. The study represents one of the largest near-atomistic simulations of a biological membrane to date. It shows how the high concentration of proteins found in the viral envelope can attenuate formation of lipid domains, which may help to explain why lipid rafts do not form on large scales in vivo.